"Ask a Professional—Ask a Librarian": Librarianship and the Chronic Struggle for Professional Status. (November 2018) - Garcia, Mattea A.; Barbour, Joshua B.
Professionalizing occupations strive to convince the public, policy makers, and each other of their distinctiveness and legitimacy. Efforts to maintain professional status are a key facet of professional identity negotiation, which is complicated by technological, political, and economic threats. This study investigated librarians' struggle to defend the legitimacy of their profession while facing threats to their status and values. Drawing on interviews ( N = 32) and observations of librarians from multiple work sites, this study provides evidence for conceptualizing professionalization as an ongoing, macrosocial, communicative process through which individuals attempt to define and defend the profession. The findings contribute to institutional and communication theory of professional identity negotiation, offering the insight that the discursive resources provided by the profession shape professionals' efforts to resist stigma facing the profession, and yet, those same professional discursive resources can make their navigation of material and discursive threats to the profession more difficult.